Norma interviewed by Lena Robinson for the Cultural context of unemployment oral history project - Norma; Robinson, Lena.; Cultural Context of Unemployment Project. Casino/Wollongong Women's Project (1985)
Norma, an Aboriginal, speaks of unemployment and Aboriginal unemployment; work experience; local young unemployed; white employers' attitudes to Aboriginal employees; why some Aboriginals don't want to work; her work aspirations; CES; background; being on the dole.
Aboriginal and Torres Strait Islander people are advised that this recording may contain names and voices of deceased persons.
Recorded by the Casino/Wollongong Women's Project of the Cultural Context of Unemployment Project, a CEP Program administered by the National Library of Australia.
Digital master available
Transcript available (8 p.)
Keywords: Norma -- Interviews; Women, Aboriginal Australian -- Employment; Women, Aboriginal Australian -- Interviews